2000
DOI: 10.1080/02643290050110629
|View full text |Cite
|
Sign up to set email alerts
|

Selective Deficit for People’s Names Following Left Temporal Damage: An Impairment of Domain-Specific Conceptual Knowledge

Abstract: As a consequence of a head trauma, APA presented with selective anomia for the names of familiar people, in the absence of comparable disorders for common names and other proper names. Face recognition was normal; and naming performance was unaffected by stimulus and response types. Selective proper name anomia was not due to effects of frequency of usage or of age of acquisition, or to selective memory/learning deficits for the names of people. Even though APA was able to provide at least some information on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(23 citation statements)
references
References 66 publications
(176 reference statements)
3
20
0
Order By: Relevance
“…Yet none of these ideas accounts for the fact that ER recognised not only body parts but also human items such as an old lady, a black boy, and a baby. His pattern of results thus seems more consistent with Shelton et al's (1998) suggestion that there is a separate network for conspecifics (see also Kay & Hanley, 1999;Miceli et al, 2000).…”
Section: Inter-category Variabilitysupporting
confidence: 79%
See 2 more Smart Citations
“…Yet none of these ideas accounts for the fact that ER recognised not only body parts but also human items such as an old lady, a black boy, and a baby. His pattern of results thus seems more consistent with Shelton et al's (1998) suggestion that there is a separate network for conspecifics (see also Kay & Hanley, 1999;Miceli et al, 2000).…”
Section: Inter-category Variabilitysupporting
confidence: 79%
“…ER's pattern of performance is consistent with the growing belief (Barbarotto et al, 2001;Caramazza, 1998;Kay & Hanley, 1999;Miceli et al, 2000;Shelton et al, 1998) that the categories of animals, plant life, conspecifics, and artefacts are dissociable. According to this taxonomic conception, there are separate subsystems of semantic representation for different categories, but there is no such separation for features: All conceptual information, both sensorial and nonsensorial, related to a particular category, is represented in the same neural network.…”
Section: Kolinsky Et Alsupporting
confidence: 78%
See 1 more Smart Citation
“…Indeed, patients with a disproportionate or selectively impaired processing of animals (Blundo, Ricci, & Miller, 2006;Caramazza & Shelton, 1998), fruit/vegetables (Hart, Berndt, & Caramazza, 1985;Laiacona, Barbarotto, & Capitani, 2005;Samson & Pillon, 2003), conspecifics (Ellis, Young, & Critchley, 1989;Miceli et al, 2000), social groups (Rumiati et al, 2014), or non-living things (Laiacona & Capitani, 2001;Sacchett & Humphreys, 1992) have been described. Moreover, Laiacona, Capitani, and Caramazza (2003) published the case of an HSE patient, E.A., who exhibited a poor recognition of living things and preserved recognition of sensoryquality categories (i.e., liquids, substances, and materials).…”
Section: The Domain-specific Hypothesismentioning
confidence: 99%
“…The semantic categories that are observed to be disproportionately impaired include conspecifics (Ellis, Young, & Critchley, 1989;Miceli, Capasso, Daniele, Esposito, Magarelli & Tomaiuolo, 2000), animals (Caramazza & Shelton 1998;Blundo, Ricci, & Miller, L. 2006), fruit and vegetables (Hart, Berndt & Caramazza, 1985;Samson & Pillon, 2003) and nonliving objects (Caramazza & Hillis, 1991;Sacchett & Humphreys, 1992;Laiacona & Capitani, 2001). Lesion-deficit correlation studies of brain damaged patients (Damasio, Grabowski, Tranel, Hichwa, & Damasio, 1996;Tranel, Damasio, & Damasio, 1997;Damasio, Tranel., Grabowski, Adolphs, & Damasio, 2004) and reviews of the available neuropsychological data (Gainotti 2000;Capitani, Laiacona, Mahon, & Caramazza, 2003) have shown that deficits for different categories of objects tend to be associated with specific loci of brain lesion, despite the fact that deficits for knowledge of a category of objects can sometimes derive from lesions to different brain areas.…”
Section: Introductionmentioning
confidence: 99%